Health literacy and mental health of school principals. Results from a German cross-sectional survey. Issue 3 (16th March 2021) - Dadaczynski, Kevin; Kotarski, Claudia; Rathmann, Katharina; Okan, Orkan
Abstract : Purpose: School principals are generally seen as key facilitators for the delivery and long-term implementation of activities on school health promotion, including health literacy. However, there is little evidence on the health literacy and health status of this occupational group. The purpose of this paper is to investigate the health literacy of school principals and its association with mental health indicators. Design/methodology/approach: A cross-sectional online survey with German school principals and members of the management board (vice principals) was conducted ( n  = 680, 68.3% female). Demographic (gender, age) and work characteristics (type of school, professional role) as well as health literacy served as independent variables. Mental health as a dependent variable included well-being, emotional exhaustion and psychosomatic complaints. Next to uni- and bivariate analysis, a series of binary logistic regression models was performed. Findings: Of the respondents, 29.2% showed a limited health literacy with significant differences to the disadvantage of male principals. With regard to mental health, respondents aged over 60 years and those from schools for children with special educational needs were less often affected by low well-being as well as frequent emotional exhaustion and psychosomatic complaints. Taking into account demographic and work characteristics, regression models revealed significant associations between a low level of health literacy and poor mental health across all indicators. Research limitations/implications: The cross-sectional nature of this study does not allow to draw conclusions about the causal pathways between health literacy and mental health. Although the sample has been weighted, the results cannot be generalized to the whole population of school principals. There is a need for evidence-based interventions aiming at promoting health literacy and mental health tailored to the needs of school principals. Originality/value: This is the first study to investigate health literacy and its association with health indicators among school principals.